2006
DOI: 10.1530/rep.1.00910
|View full text |Cite
|
Sign up to set email alerts
|

Expression of caspase-2, -3, -8 and -9 proteins and enzyme activity in the corpus luteum of the rat at different stages during the natural estrous cycle

Abstract: Apoptosis is associated with the regression of the corpus luteum (CL) in many species. Since caspases play a central role in apoptosis, we studied several initiators (-2, -8, and -9) and the main effector (-3) caspase in the CL during the estrous cycle of the rat. Two different populations of CL (old and new) were identified on ovaries at estrus and diestrus II (DII). Diminished (P!0.05) luteal progesterone content and P450scc levels suggested that functional luteolysis occurred between the new CL at DII and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…A study in pregnant Sprague-Dawley rats showed an increase in the activity of caspases 2, 8 and 9 that corresponded to the peak concentration of progesterone in the pregnant females, resulting in an increase in the number of apoptotic cells in the ovary (23). Our assumption is in accordance with these results, in terms of the increase in apoptotic cells in the presence of progesterone.…”
Section: -------------------------------------------------supporting
confidence: 88%
“…A study in pregnant Sprague-Dawley rats showed an increase in the activity of caspases 2, 8 and 9 that corresponded to the peak concentration of progesterone in the pregnant females, resulting in an increase in the number of apoptotic cells in the ovary (23). Our assumption is in accordance with these results, in terms of the increase in apoptotic cells in the presence of progesterone.…”
Section: -------------------------------------------------supporting
confidence: 88%
“…Moreover, depending on the balance between pro-and antiapoptotic proteins, the initiator CASPASE9 is activated and several effector caspases such as CASPASE3 (CASP3) or CASPASE7 are sequentially activated and promote apoptosis in various systems (Budihardjo et al 1999). In previous studies, we reported the expression and activation of proapoptotic caspase-mediated pathways during both spontaneous luteolysis in pregnancy and natural cycles, and PGF2a-induced luteolysis (Peluffo et al 2006, Hernandez et al 2009). In addition, different reports have demonstrated the interaction between the Notch signaling and PI3K/ AKT pathways in cancer cells (Meurette et al 2009, Wang et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Its main function, progesterone (P 4 ) production, allows for the maintenance of pregnancy [1]. In the absence of gestation, CL regression, which is characterized by changes and degeneration of both vascular and steroidogenic cells, is essential for normal ovarian cyclicity and resumption of a new estrous cycle [2][3][4].…”
Section: Introductionmentioning
confidence: 99%